State policy on cultural heritage protection in Tatarstan during 1970-ies - A. Litvin, Aleksandr (2018)
1970-ies are an important period of Soviet history concerning the protection of monuments. By this time, the protection of monuments in the USSR went beyond the competence of only state bodies, an active role in cultural heritage preservation was played by the public. All-Russian Society for the Protection of Monuments (VOOPIiK), established in 1966, performed its work. In Tatarstan, this society was established on February 8, 1966. It 1970-ies they adopt the law in the country (The law of the USSR "On the Protection and the Use of Historical and Cultural Monuments" issued on October 29, 1976) [1] regulating this sphere. It becomes the first comprehensive state document on the protection of monuments. In TASSR, the protection of monuments, and decisions taken in this area, corresponded to the general state policy for the preservation of the historical and the cultural heritage of the USSR. Some progress was made, but many problems remained unresolved.